Neonatal & Pediatric Dermatology of Scabies: A Literature Review - Hairy, Fathinah Salsabilla; Rahman, Hadian (Jurnal Biologi Tropis, 2025)
Scabies is a contagious disease caused by the Sarcoptes scabiei var.hominis mite which commonly occurs in neonates and children due to close physical contact and low immune systems. Scabies disease can be found throughout the world without influence by age, race, and socio-economic conditions of the community. Scabies is transmitted through direct skin contact, with a higher risk in environments with poor sanitation. Clinical symptoms that may appear include itching that worsens at night, the formation of papules and burrows. In neonates or infants, symptoms such as crying and restlessness may occur, while in older children, symptoms such as insomnia, fatigue, and lethargy due to itching at night may occur. This paper aims to provide a comprehensive understanding of the epidemiology, diagnosis, and management of scabies. The writing method used in this literature review is based on references from various sources in Indonesian and English literature. The results of this literature review scabies is a contagious disease caused by the Sarcoptes scabies var hominis which can occur worldwide with a life cycle that occurs on human skin. The diagnosis of scabies can be confirmed by the discovery of two of the four presumptive diagnoses. Management of scabies focuses on preventing the spread, reducing risk factors, and supporting pharmacological treatment. Scabies is a parasitic infection that affects a person's quality of life.